2018
DOI: 10.1021/acssuschemeng.8b02118
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Carbonization of Fructose: Growth Mechanism and Kinetic Model

Abstract: Hydrothermal carbonization experiments were performed with fructose solutions as feedstock. A kinetic model is proposed that models hydrochar formation based on molar concentrations. On the basis of SEM pictures, the mean particles size of the hydrochar was determined, and it could be demonstrated that the growth of the particles is not directly related to the formation rate of hydrochar or the decreasing rate of the intermediates concentration in the aqueous solution. Four additives (salts) have been tested, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
89
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 84 publications
(102 citation statements)
references
References 74 publications
9
89
2
Order By: Relevance
“…While for real biomass it could be demonstrated that the lignin content significantly affects yield and properties of the hydrochar, humin obtained from the hydrothermal treatment of pure sugars is considered polycondensated HMF. This is evident from the elemental composition of humin, which complies well with HMF minus one water molecule . What kind of condensation reaction takes place, is still matters of discussion.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…While for real biomass it could be demonstrated that the lignin content significantly affects yield and properties of the hydrochar, humin obtained from the hydrothermal treatment of pure sugars is considered polycondensated HMF. This is evident from the elemental composition of humin, which complies well with HMF minus one water molecule . What kind of condensation reaction takes place, is still matters of discussion.…”
Section: Discussionmentioning
confidence: 88%
“…When performing hydrothermal treatment of sugars or biomass, a solid, insoluble by‐product is usually observed, which is labelled as humin or hydrochar. Hydrochar is characterised by a high carbon content of around 67 % w/w . Hence, the hydrothermal carbonisation especially of agricultural residues features a field of growing importance in order to produce absorbents, fertilizers etc.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations